The evaluation of activity of selected lactic acid bacteria for bioconversion of milk and whey from goat milk to release biomolecules with antibacterial activity - Biadała, Agata; Szablewski, Tomasz; Cegielska-Radziejewska, Renata; Lasik-Kurdyś, Małgorzata; Mohd Adzahan, Noranizan (MDPI, 2023)
The aim of the study was to assess the antibacterial features of functional macromolecules released during the fermentation of goat milk and whey from goat milk by selected lactic acid bacteria strains that are components of kefir grain microflora. Two milk sources were used: goat milk and whey from goat milk. The lactic acid bacteria (LAB) and indicator microorganisms used were Lactobacillus plantarum PCM 1386, Lactobacillus fermentum PCM 491, Lactobacillus rhamnosus PCM 2677, Lactobacillus acidophilus PCM 2499, Escherichia coli PCM 2793, Salmonella enteritidis PCM 2548, Micrococcus luteus PCM 525, and Proteus mirabilis PCM 1361. The metabolic activity of LAB was described by the Gompertz model, and the parameters proposed for this experiment were the maximum rate of change of electrical impedance and potential biodegradability. Antibacterial activity was examined using the culture method in a liquid medium, determination of the reduction in indicator microorganisms, and optical density changes. Results show that the selective LAB produced certain active biomolecules with antibacterial activity from whey, a by-product that is sometimes troublesome for goat milk processors to manage. Lactobacillus acidophilus is a microorganism that is characterized by the highest metabolic activity in goat milk and whey from goat milk. It has the possibility to produce macromolecules with antibacterial activity.